Which firms benefit from foreign direct investment? Empirical evidence from Indonesian manufacturing - Suyanto; Salim, Ruhul; Bloch, Harry (Elsevier, 2014)
Despite growing concern regarding the productivity benefits of foreign direct investment (FDI), very few studies have been conducted on the impact of FDI on firm-level technical efficiency. This study helps fill this gap by empirically examining the spillover effects of FDI on the technical efficiency of Indonesian manufacturing firms. A panel data stochastic production frontier (SPF) method is applied to 3318 firms surveyed over the period 1988–2000. The results reveal evidence of positive FDI spillovers on technical efficiency. Interesting differences emerge however when the samples are divided into two efficiency levels. High-efficiency domestic firms receive negative spillovers, in general, while low-efficiency firms gain positive spillovers. These findings justify the hypothesis of efficiency gaps, that the larger is the efficiency gap between domestic and foreign firms the easier the former extracts spillover benefits from the latter.